Native plant community recovery after Carpobrotus (ice plant) removal on an island — results of a 10‐year project. Issue 1 (27th September 2020) - Buisson, Elise; Braschi, Julie; Chenot‐Lescure, Julie; Hess, Manon Célia Morgane; Vidaller, Christel; Pavon, Daniel; Ramone, Hervé; Amy‐Krebs, Elise; Cottaz, Cyril; Passetti, Aurélie; Aboucaya, Annie; Affre, Laurence
Abstract: Question: Species of the genus Carpobrotus, or ice plant, are succulent mat‐forming perennial herbs often introduced for soil stabilization. They are common in coastal environments and may thus threaten island biodiversity. While their effects are well known on soils, plant communities and associated fauna, the effects of Carpobrotus control on vegetation recovery are poorly documented. The aim of the paper is to describe plant community trajectories after Carpobrotus removal. Location: Bagaud: a 58‐ha Mediterranean island, southern France. Methods: Carpobrotus and its litter were removed in 2011–2012. Follow‐up controls of germinations and resprouts were carried out from then on. Plant communities were surveyed every year two years before and seven years after Carpobrotus removal: on two ca. 0.5‐ha sites (one coastal and one inland) and in three native plant communities used as potential references. Differences in resprouts, vegetation parameters, and Bray–Curtis similarity indices between years were tested. Plant community dynamics was studied through a non‐metric multidimensional scaling and two recovery indices. Results: The removal of Carpobrotus and its litter led to the recovery of diverse native plant communities. To prevent Carpobrotus return and ensure success, follow‐up controls were necessary for a period of at least seven years, but the amount of work decreased with time. The plant community recovering on the coastal site quickly reached a composition and structure similar to that of non‐invaded coastal vegetation, although some slow‐growing native species remain underrepresented (e.g., Crithmum maritimum and Limonium pseudominutum ). The plant community recovering on the inland site was still very different from the surrounding matorral vegetation because of its slow colonization dynamics, particularly in the presence of competitive herbaceous species. Conclusion: Both sites now provide diverse native plant communities with a more diversified composition and structure (plant heights, litter, bare ground patches) than the plant communities which used to be associated with Carpobrotus mats. Abstract : The removal of Carpobrotus and its litter in areas with no other invasive species in the surroundings can quickly lead to diverse native plant communities. Coastal vegetation may recover and be relatively similar to the reference in a few years. Plant communities with more shrubs may need more time to recover. To prevent Carpobrotus return, germination and resprout removal is essential.